Development of a Postbiotic-Based Orodispersible Film to Prevent Dysbiosis in the Oral Cavity - Rebelo, Mariana B; Oliveira, Cláudia S; Tavaria, Freni K (Frontiers in bioscience (Elite edition), 2025)
Background: Oral diseases affect over three billion peopleand are among the most commonly observed infections worldwide. Recent studies have shown that controlling the ecology of the oralome is more effective in reducing the risk of caries than the complete removal of both harmful and beneficial microorganisms. This work aimed to develop a strategy for preventing dysbiosis in the oral cavity by applying a postbiotic-based orodispersible film. Methods: Lactiplantibacillus plantarum 226V and Lacticaseibacillus paracasei L26 were cultured in De Man–Rogosa–Sharpe (MRS) broth for 48 hours, followed by centrifugation and filtration. Then, the resultant postbiotics were then subjected to various dilutions (10% (v/v), 20% (v/v), 40% (v/v), 60% (v/v) and 100% (v/v)) and co-incubated with Streptococcus mutans. Antimicrobial efficacy, minimal inhibitory concentration, the time required to inhibit S. mutans growth, and antibiofilm properties of the postbiotics were assessed. Subsequently, an orodispersible film comprising polymers and plasticizers, namely Xanthan gum, maltodextrin, and glycerol, was developed as a vehicle for postbiotic delivery. Formulation optimization, physical property evaluation, and cytotoxicity against the TR146 human oral cell line (TR146 cell line) were conducted. Results: Postbiotics demonstrated antimicrobial and antibiofilm activity against S. mutans following 24-hour co-incubation. The minimal inhibitory concentration for combined postbiotics administration was 20% (v/v). Remarkably, 79.6 ± 8.15% inhibition of biofilm formation was achieved using 100% (v/v) of the postbiotic derived from L. plantarum 226V. Incorporating postbiotics did not compromise the dissolution time of orodispersible films, all exceeding 20 minutes. Furthermore, solubility improved following postbiotic addition, facilitating ease of handling. Importantly, postbiotic-impregnated orodispersible films were non-cytotoxic when exposed to the TR146 cell line. Conclusions: These findings underscore the potential of orodispersible films loaded with postbiotics as a promising potential intervention for oral dysbiosis.